BUILDING CIVILIZATION FROM PESANTREN: INTEGRATING VALUE-BASED EDUCATION, SOCIAL INCLUSION, AND GLOBAL COMPETITIVENESS - Lukman Nul Hakim; Ahmad Musaddad (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Islamic boarding schools (pesantren) in Indonesia possess strategic potential inshaping inclusive, value-driven, and globally competitive communities. This articleexplores the educational transformation within pesantren, emphasizing valueeducation, soft skill enhancement, and digital responsiveness. Drawing on librarybased research, the study finds that pesantren have increasingly adopted digital literacy, entrepreneurial curricula, and inclusive practices for marginalized groups. The leadership of kyai remains a key factor in cultivating resilient and empathetic student character. These findings underscore pesantren's role in fostering sustainable development and social justice. Nevertheless, limitations in infrastructure andinstitutional typology highlight the need for further empirical research to enrich educational reform within Islamic contexts